Autoantibodies in Systemic Sclerosis: Unanswered Questions - Kayser, Cristiane; Fritzler, Marvin J. (Frontiers in Immunology, 2015)
Systemic sclerosis (SSc) is an autoimmune disease characterized by vascular abnormalities, and cutaneous and visceral fibrosis. Serum autoantibodies directed to multiple intracellular antigens are present in more than 95% of patients and are considered a hallmark of SSc. They are helpful biomarkers for the early diagnosis of SSc and are associated with distinctive clinical manifestations. With the advent of more sensitive, multiplexed immunoassays, new and old questions about the relevance of autoantibodies in SSc are emerging. In this review we discuss the clinical relevance of autoantibodies in SSc emphasizing the more recently published data. Moreover, we will summarize recent advances regarding the stability of SSc autoantibodies over the course of disease, whether they are mutually exclusive and their potential roles in the disease pathogenesis.